Pharrajimos : the fate of the Roma during the Holocaust - Bársony, János, 1951-; Daróczi, Ágnes (New York : International Debate Education Association, 2008)
"Pharrajimos: The Fate of the Roma During the Holocaust recounts the largely unknown history of the Hungarian Roma during World War II. The anthology offers readers chronologies of the Pharrajimos in the Third Reich and in Hungary; general background on the Roma in Europe before and during World War II; detailed accounts of the Pharrajimos in Hungary - the initiatives of Laszló Endre, the mass murder of Gypsies at Várpalota and Inota-Lake Grábler, and the events at Komáromi Csillagerőd - and the Holocaust in Gypsy folk poetry. Twelve oral histories also present first-hand accounts of the survivors. The work includes a detailed list of events by location as well as a series of appendixes on the struggle to raise awareness of the Pharrajimos."--BOOK JACKET.
Chronology. The Pharrajimos in the Third Reich ; The Pharrajimos in Hungary -- 20th century Roma history and the Pharrajimos -- Anti-Gypsy initiatives and raids in Pest County under Deputy-Lieutenant Laszló Endre (1928, 1939-1944) -- The mass murder of Gypsies at Várpalota and Inota-Lake Grábler at the end of January 1945 -- One of the Roma killing fields : Komáromi Csillagerőd, autumn, 1944 -- The Holocaust in Gypsy Folk Poetry -- Oral history : personal statements of the survivors.
First published in Hungarian as Pharrajimos : romák sorsa a nácizmus idején. L'Harmattan, 2004.
Translator from t.p. verso.
Includes bibliographical references.
HU OSA 207 - Donation of the Open Society Institute-Budapest
Keywords: Romanies -- Nazi persecution -- Hungary; Romanies -- Hungary; Holocaust, Jewish (1939-1945) -- Hungary -- Personal narratives